Composite nanoparticle, carrier delivery system, pharmaceutical composition, cosmetic, nutritional health-care product and preparation method and application of composite nanoparticle, carrier delivery system, pharmaceutical composition, cosmetic and nutritional health-care product

Through the modification of fructan and ionic polymers, the stability of zein nanoformula under environmental pressure was solved, and the efficient loading and antioxidant activity was improved. It is suitable for food, health products and drugs Development.

CN119112830AActive Publication Date: 2024-12-13GUANGXI BOTANICAL GARDEN OF MEDICINAL PLANTS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411022406.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2024-12-13
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

Zein nanoformulations have poor stability under ambient pressures (such as pH, ionic strength, and thermal processing), limiting their use in pharmaceuticals, functional foods and cosmetics.

Method used

Fructan (P-FOS) and ionic polymers (such as sodium caseinate) are used to modify zein protein to form composite nanoparticles, which are prepared by anti-solvent co-assembly and precipitation method to improve the stability and packaging of nanoparticles. Loading efficiency.

Benefits of technology

It significantly improves the stability and redispersion of nanoparticles under different environmental pressures, enhances the loading and drug loading efficiency of active ingredients, improves bioavailability, and significantly improves antioxidant activity in simulated gastrointestinal fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119112830A_ABST
    Figure CN119112830A_ABST
Patent Text Reader

Abstract

The invention discloses a composite nanoparticle, a carrier delivery system, a pharmaceutical composition, cosmetics, a nutritional health-care product and a preparation method and application, and belongs to the technical field of nano carrier delivery systems.The composite nanoparticle comprises a core particle formed by zein; and the coating layer is formed by fructan and an ionic polymer. The fructan and casein co-modified zein core / shell nanoparticles are developed for the first time, can be used for efficiently entrapping hydrophobic active ingredients such as astilbin, and can obviously enhance the redispersibility of the zein composite nanoparticles and the stability of the zein composite nanoparticles under different environmental pressures (pH, temperature, ionic strength and the like); the entrapment and drug loading efficiency of the active ingredients and the absorption distribution of the active ingredients in vivo are improved, so that the bioavailability of the active ingredients is improved. The nanoparticles prepared by the invention are expected to become an effective hydrophobic active ingredient carrier for development of food, health care products, cosmetics and medicines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocarrier delivery systems, and specifically to a composite nanoparticle, a carrier delivery system, a pharmaceutical composition, a cosmetic, a nutritional health product, and a preparation method and application thereof. The present invention relates to a method and application of surface modification of zein to increase the stability of nanoparticle carriers, and more specifically to fructan (P-FOS)-modified astilbin (Ast) / zein / sodium caseinate (NaCas) composite nanoparticles, a carrier delivery system, a pharmaceutical composition, a cosmetic, a nutritional health product, and a preparation method and application thereof. Background Art

[0002] Zein is a widely used nano-delivery biomaterial that is increasingly popular in the fields of food, cosmetics, health food, and pharmaceuticals due to its unique advantages such as biodegradability, biocompatibility, and oral application. Zein or zein micro / nanoparticles encapsulated with bioactive ingredients can help implement many nutrition and health strategies in the above fields. However, such zein-based micro / nanoparticles have poor stability and redispersibility under various environmental stress challenges, such as pH, ionic strength, and thermal processing. In particular, zein nanoformulations denature and aggregate during thermal processing, which has a negative impact on the production control and quality of the product, limiting its practical application.

[0003] Therefore, new materials and strategies are urgently needed to modify zein nanoformulations to address these issues and expand the application of zein nanocarrier systems in the pharmaceutical, functional food, cosmetic, and nutritional supplement industries. Summary of the invention

[0004] In view of the above problems, the present invention provides a zein composite nanoparticle modified with fructan and an ionic polymer and a carrier delivery system thereof, as well as a preparation method and application of the same.

[0005] In order to achieve these objectives of the present invention, in a first aspect, the present invention provides a composite nanoparticle comprising:

[0006] core particles, formed by zein;

[0007] The coating layer is formed by fructan and ionic polymer.

[0008] Specifically, the ionic polymer can be a protein, a polypeptide / oligopeptide, an ionic polysaccharide / oligosaccharide, and related synthetic ionic polymers. Preferred is sodium caseinate.

[0009] Specifically, the average molecular weight of the fructan is 800-150000Da, for example, 1000, 2000, 5000, 10000, 20000, 50000, 80000, 90000, 100000, 110000, 150000Da, especially 800-5000Da. In some embodiments of the invention, the average molecular weight of the fructan is 1600Da.

[0010] Specifically, the particle size of the composite nanoparticles can be 100, 120, 130, 150, 160, 170, 180, 190, 200, 220, 250, 300 nm), especially 100-180 nm.

[0011] Specifically, the coating layer may have a thickness of 1-100 nm, for example, 10, 18, 20, 22, 24, 25, 26, 28, 30, 40, 50, 60, 70, 80, 90, 100 nm, particularly 10-50 nm.

[0012] Specifically, the particle size of the core particles in the composite nanoparticles can be 50-120 nm (e.g., 50, 60, 70, 80, 85, 86, 88, 90, 92, 94, 96, 98, 100 nm), especially 85-95 nm.

[0013] Specifically, the composite nanoparticles are spherical.

[0014] Specifically, the composite nanoparticles are negatively charged.

[0015] In a second aspect of the present invention, a method for preparing the composite nanoparticles is provided, comprising:

[0016] (1) forming the core particles;

[0017] (2) Forming the coating layer.

[0018] Specifically, the core particles are formed by an anti-solvent co-assembly precipitation method. More specifically, step (1) comprises: dissolving zein in an ethanol aqueous solution; adjusting the pH to acidic. Preferably, the ethanol aqueous solution can be a 70-95% (v / v) ethanol aqueous solution, in particular a 75% ethanol aqueous solution. Preferably, adjusting the pH to acidic is adjusting the pH to 3.5-6.5 (e.g., 3.5, 4.5, 5, 5.2, 5.5, 5.7, 6, 6.5). Preferably, the reagent used to adjust the pH to acidic is an inorganic acid solution, such as a hydrochloric acid solution.

[0019] Specifically, step (1) also includes a stirring step; more specifically, the stirring speed can be 500-5000 rpm (e.g., 500, 1000, 2000, 3000, 4000, 5000 rpm), and the stirring time can be 10-60 minutes (e.g., 10, 20, 30, 40, 50, 60 minutes).

[0020] In one embodiment of the present invention, step (1) comprises: dissolving zein in an ethanol aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a core particle solution.

[0021] Specifically, the concentration of zein in the core particle solution can be 1-70% (w / v) (e.g., 1%, 5%, 7.5%, 10%, 20%, 25%, 40%, 50%, 60%), particularly 20-60%, more particularly 20-40%; in some embodiments of the present invention, the concentration of zein is 20%.

[0022] Specifically, step (2) comprises: dissolving fructan and ionic polymer in aqueous solution; in one embodiment of the present invention, step (2) comprises: dissolving fructan and sodium caseinate in aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a coating solution.

[0023] Specifically, the pH of the coating solution is acidic, for example, pH 2-6 (eg, 2, 3, 4, 5, 6).

[0024] Specifically, step (2) also includes a stirring step; more specifically, the stirring speed can be 500-5000 rpm (e.g., 500, 1000, 2000, 3000, 4000, 5000 rpm), and the stirring time can be 30-720 minutes (e.g., 30, 60, 120, 240, 360, 720 minutes).

[0025] Specifically, the fructan concentration in the coating solution can be 1-70% (w / v) (e.g. 1%, 5%, 7.5%, 10%, 20%, 25%, 40%, 50%, 60%), particularly 20-60%, more particularly 30-50%; in some embodiments of the present invention, the fructan concentration is 50%.

[0026] Specifically, the concentration of the ionic polymer in the coating solution can be 1-80% (w / v) (e.g., 1%, 5%, 7.5%, 10%, 20%, 25%, 40%, 50%, 60%, 70%, 80%), particularly 20-60%, more particularly 30-50%; in some embodiments of the present invention, the concentration of sodium caseinate is 50%.

[0027] Specifically, the average molecular weight of fructan is 800-150000 Da, (e.g., 800, 1000, 2000, 5000, 10000, 20000, 50000, 80000, 90000, 100000, 110000, 150000 Da), in particular 800-5000 Da. In some embodiments of the present invention, the average molecular weight of fructan is 1600 Da.

[0028] Specifically, the method further comprises step (3): mixing the core particle solution obtained in step (1) with the coating layer solution obtained in step (2).

[0029] Optionally, step (3) further includes removing impurities.

[0030] Specifically, step (3) also includes a stirring step; more specifically, the stirring speed can be 500-5000 rpm (e.g., 500, 1000, 2000, 3000, 4000, 5000 rpm), and the stirring time can be 30-240 minutes (e.g., 30, 40, 60, 80, 100, 120, 240 minutes).

[0031] Specifically, step (3) comprises: adding the core particle solution obtained in step (1) to the coating layer solution obtained in step (2), adjusting the pH to acidic, for example, pH 2-6 (for example, 2, 3, 4, 5, 6), and stirring to obtain a solution system. Preferably, ethanol is further removed.

[0032] Specifically, step (3) further comprises removing impurities, and the solution system obtained in step (3) is centrifuged to remove impurities.

[0033] In the third aspect of the present invention, there is provided the use of the nanoparticles as drug carriers or in the preparation of drugs or cosmetics or health foods.

[0034] In the fourth aspect of the present invention, a carrier delivery system is provided, which has sustained release and targeting properties, and is the nanoparticle or contains the nanoparticle, wherein the nanoparticle has a core particle and a coating layer coated on the outer surface of the core particle, wherein the core particle contains zein, and the coating layer contains fructan and an ionic polymer; and the core particle is loaded with one or more active ingredients.

[0035] In one embodiment of the present invention, the core particle is formed of zein and an active ingredient.

[0036] In one embodiment of the present invention, the coating layer is formed of fructan and sodium caseinate.

[0037] Specifically, the average molecular weight of fructan is 800-150000 Da, (e.g., 800, 1000, 2000, 5000, 10000, 20000, 50000, 80000, 90000, 100000, 110000, 150000 Da), in particular 800-5000 Da. In some embodiments of the present invention, the average molecular weight of fructan is 1600 Da.

[0038] Specifically, the particle size of the nanoparticles can be 100, 120, 130, 150, 160, 170, 180, 190, 200, 220, 250, 300 nm, especially 100-180 nm.

[0039] Specifically, the coating layer may have a thickness of 1-100 nm, (e.g., 10, 18, 20, 22, 24, 25, 26, 28, 30, 40, 50, 60, 70, 80, 90, 100 nm), in particular 10-50 nm.

[0040] Specifically, the core particle in the nanoparticle can be 50-120nm (e.g., 50, 60, 70, 80, 85, 86, 88, 90, 92, 94, 95, 96, 98, 100nm), especially 85-95nm.

[0041] Specifically, the nanoparticles are spherical.

[0042] Specifically, the nanoparticles are negatively charged.

[0043] In one embodiment of the present invention, the above-mentioned active ingredients can be active ingredients of foods, nutritional supplements, for example, curcumin, vitamin E, lutein, β-carotene and the like.

[0044] In one embodiment of the present invention, the above-mentioned active ingredients can be cosmetic active ingredients, for example, glutathione, kojic acid, tranexamic acid, salicylic acid, niacinamide, fruit acid, azelaic acid, vitamin A and its derivatives, vitamin C, glycerin, hyaluronic acid, sodium pyrrolidone carboxylate, natural moisturizing factor, ceramide, collagen, lactic acid, urea, chitosan derivatives, aloe vera, seaweed extract, polyglutamic acid, jojoba oil, squalene, shea butter, etc.

[0045] In one embodiment of the present invention, the above-mentioned active ingredients can be pharmaceutical active ingredients, such as doxorubicin, epirubicin, pirarubicin, idarubicin; mitoxantrone; topotecan, irinotecan, isotecan, aminocamptothecin; paclitaxel, docetaxel; gefitinib, imatinib, nilotinib, sunitinib, lapatinib, tofacitinib, crizotinib, masitinib, entrectinib, ibrutinib, afatinib, flumatinib, erlotinib, neratinib, alectinib, apatinib, talazoparib, Lorlatinib, TPX-0005; cisplatin, carboplatin, nedaplatin, cycloplatin, oxaliplatin, lobaplatin; vinblastine, vincristine, vinorelbine, berberine, berbamine; honokiol (HNK); uracil mustard, nitrogen mustard, ifosfamide, melphalan, chlorambucil, pipobroman, trothamide, triethylenethiophosphoramide, busulfan, carmustine, lomustine, streptozocin, dacarbazine, fluorouracil deoxyribonucleoside, cytarabine, 6-mercaptopurine, 6-thioguanine, fludarabine phosphate; etc.

[0046] Specifically, in the core particle, the weight ratio of zein to the active ingredient can be 1:1 to 100:1 (e.g., 1:1, 2:1, 5:1, 10:1, 15:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1), especially 1:1 to 5:1.

[0047] In one embodiment of the present invention, the active ingredient is astilbin (Ast); more specifically, in the core particles, the weight ratio of zein to astilbin is 2:1.

[0048] In a fifth aspect of the present invention, a method for preparing the carrier delivery system is provided, comprising the following steps:

[0049] (1) Forming core particles;

[0050] (2) Forming a coating layer.

[0051] Specifically, the core particles are formed by an anti-solvent co-assembly precipitation method. More specifically, step (1) comprises: dissolving zein and the active ingredient (separately or together) in an ethanol aqueous solution, and adjusting the pH to acidic. Specifically, the ethanol aqueous solution can be a 70-95% (v / v) ethanol aqueous solution, in particular a 75% ethanol aqueous solution. Specifically, adjusting the pH to acidic is adjusting the pH to 3.5-6.5 (e.g., 3.5, 4.5, 5, 5.2, 5.5, 5.7, 6, 6.5). Specifically, the reagent used to adjust the pH to acidic is an inorganic acid solution, such as a hydrochloric acid solution. Specifically, step (1) also includes a stirring step; more specifically, the stirring speed can be 500-5000 rpm (e.g., 500, 1000, 2000, 3000, 4000, 5000 rpm), and the stirring time can be 10-60 minutes (e.g., 10, 20, 30, 40, 50, 60 minutes).

[0052] In one embodiment of the present invention, step (1) comprises: dissolving zein and the active ingredient (separately or together) in an ethanol aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a core particle solution.

[0053] Specifically, the concentration of zein can be 1-70% (w / v) (e.g., 1%, 5%, 7.5%, 10%, 20%, 25%, 40%, 50%, 60%), particularly 20-60%, more particularly 10-40%; in some embodiments of the present invention, the concentration of zein is 20%.

[0054] Specifically, step (2) comprises: dissolving fructan and ionic polymer in aqueous solution; in one embodiment of the present invention, step (2) comprises: dissolving fructan and sodium caseinate in aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a coating solution.

[0055] Specifically, the pH of the fructan solution is acidic, for example, pH 2-6 (e.g., 2, 3, 4, 5, 6). Specifically, the stirring speed can be 500-5000 rpm (e.g., 500, 1000, 2000, 3000, 4000, 5000 rpm), and the stirring time can be 30-720 minutes (e.g., 30, 60, 120, 240, 360, 720 minutes).

[0056] Specifically, the fructan concentration can be 1-70% (w / v) (e.g., 1%, 5%, 7.5%, 10%, 20%, 25%, 30%, 40%, 50%, 60%, 70%), particularly 20-60%, more particularly 30-50%; in some embodiments of the present invention, the concentration of the fructan solution is 50%.

[0057] Specifically, the concentration of the ionic polymer solution can be 1-80% (w / v) (e.g. 1%, 5%, 7.5%, 10%, 20%, 25%, 40%, 50%, 60%, 80%), particularly 20-60%, more particularly 30-50%; in some embodiments of the present invention, the concentration of the sodium caseinate solution is 50%.

[0058] Specifically, the average molecular weight of fructan is 800-150000 Da, (e.g., 800, 1000, 2000, 5000, 10000, 20000, 50000, 80000, 90000, 100000, 110000, 150000 Da), in particular 800-5000 Da. In some embodiments of the present invention, the average molecular weight of fructan is 1600 Da.

[0059] Specifically, step (3) is also included: adding the core particle solution obtained in step (1) to the coating solution obtained in step (2). Preferably, step (3) also includes adjusting the pH to acidic, for example, pH 2-6 (for example, 2, 3, 4, 5, 6). Preferably, step (3) also includes a stirring step; more specifically, the stirring speed can be 500-5000rpm (for example, 500, 1000, 2000, 3000, 4000, 5000rpm), and the stirring time can be 30-240 minutes (for example, 30, 40, 60, 80, 100, 120, 240 minutes). Preferably, step (3) also includes removing ethanol.

[0060] In some embodiments of the present invention, step (3) comprises: adding the zein ethanol solution (core particle solution) obtained in step (1) to the fructan and ionic polymer aqueous solution (coating layer solution) obtained in step (2), adjusting the pH to acidic, stirring to obtain a solution system, and removing ethanol.

[0061] Optionally, step (3) further comprises removing impurities. Specifically, the solution system obtained in step (3) is centrifuged to remove impurities.

[0062] In the sixth aspect of the present invention, there is provided an application of the carrier delivery system in improving any one or more properties of the stability or redispersibility or encapsulation rate or release efficiency or pharmacological activity of drug-encapsulated components.

[0063] Or, the carrier delivery system is used to improve any one or more properties of the stability, redispersibility, encapsulation rate, release efficiency or activity of food, health care products and cosmetics.

[0064] Specifically, the activity refers to the activity or physiological functionality of additives allowed in health foods, such as vitamin supplements, mineral supplements, etc.

[0065] Specifically, the pharmacological activity can be anti-oxidation, anti-inflammatory, immunomodulatory, antibacterial, etc.

[0066] Specifically, the agent can be one or more of an agent for improving the stability of encapsulated components (such as a stabilizer), an agent for improving redispersibility (such as a dispersant), an agent for improving encapsulation rate and release efficiency (such as a drug carrier product), and an agent for improving pharmacological activity (such as a synergist).

[0067] In the seventh aspect of the present invention, a pharmaceutical composition is provided, which comprises the carrier delivery system described in the fourth aspect, and one or more pharmaceutically acceptable excipients.

[0068] Specifically, the pharmaceutically acceptable excipient refers to conventional excipients in the pharmaceutical field, especially pharmaceutically acceptable injection excipients, such as isotonic sterile saline solutions (sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium chloride, potassium chloride, calcium chloride, magnesium chloride, etc., or mixtures of the above salts), or dried compositions such as freeze-dried compositions, which are appropriately formed into injectable solutes by adding sterile water or physiological saline.

[0069] Specifically, the pharmaceutical composition can be administered by any suitable route, such as gastrointestinal administration or parenteral administration (e.g., intravenous, intramuscular, subcutaneous, intraorgan, intranasal, intradermal, instillation, intracerebral, rectal, etc.); the above-mentioned drug can be in any suitable dosage form, such as a dosage form for gastrointestinal administration, for example, including but not limited to tablets, pills, powders, granules, capsules, lozenges, syrups, liquids, emulsions, suspensions, etc.; a dosage form for parenteral administration, for example, an injection dosage form : such as injections (for example, for subcutaneous injection, intravenous injection, intramuscular injection, intraperitoneal injection), respiratory tract administration dosage forms: such as sprays, aerosols, powder sprays, etc., skin administration dosage forms, such as external solutions, lotions, ointments, plasters, pastes, patches, etc., mucosal administration dosage forms: such as eye drops, eye ointments, nasal drops, gargles, sublingual tablets, etc., cavity administration dosage forms: such as suppositories, aerosols, effervescent tablets, drops, pills, etc., for rectum, vagina, urethra, nasal cavity, ear canal, etc. Preferably, the pharmaceutical composition is oral.

[0070] Specifically, various dosage forms of the pharmaceutical composition can be prepared according to conventional production methods in the field of pharmacy and food, such as mixing the carrier delivery system with one or more pharmaceutically acceptable excipients, and then preparing it into the desired dosage form.

[0071] In an eighth aspect of the present invention, a food nutritional supplement is provided, comprising the carrier delivery system described in the fourth aspect, and one or more excipients acceptable for food nutritional supplements.

[0072] The acceptable auxiliary materials for food and nutritional health products refer to the conventional auxiliary materials in the field of food and nutritional health products, for example, starch, lactose, cellulose, sweeteners, colorants and the like.

[0073] In the ninth aspect of the present invention, a cosmetic is provided, comprising the carrier delivery system described in the fourth aspect, and one or more cosmetically acceptable excipients.

[0074] The cosmetically acceptable excipients refer to the conventional excipients in the cosmetic field, for example, glycerin, hyaluronic acid, vegetable oils and fats, emulsifiers, thickeners, preservatives, pigments, flavors, and the like.

[0075] The present invention has developed a zein core / shell nanoparticle co-modified with fructan (P-FOS) and protein for the first time, which can be used for efficient encapsulation of hydrophobic active ingredients (such as astilbin (Ast)), and can significantly enhance the stability of zein under different environmental pressures (pH, temperature, ionic strength), improve the encapsulation and drug loading efficiency of active ingredients, and the absorption distribution in the body, thereby improving the bioavailability of active ingredients. Taking Ast as an example, experiments have shown that Ast / zein / fructan / sodium caseinate nanoparticles have significantly enhanced stability and redispersibility under different environmental pressures (pH, temperature, ionic strength). In addition, Ast / zein / fructan / sodium caseinate nanoparticles significantly improve the dissolution and release of Ast in simulated gastrointestinal fluid, and produce stronger antioxidant activity. Therefore, the nanoparticles prepared by the present invention are expected to become an effective hydrophobic active ingredient carrier for food, health products, cosmetics and drug development.

[0076] The present invention has at least the following beneficial effects:

[0077] 1. The present invention overcomes the shortcomings of the prior art and for the first time utilizes the self-assembly structural characteristics of the natural neutral polysaccharide - fructan to develop a new type of zein composite nano-preparation physical cross-linking stabilizer, and adopts a new anti-solvent co-assembly precipitation strategy, which does not require the introduction of chemical cross-linking agents and can significantly improve the stability of zein composite nanoparticles. The preparation method is simple, which expands the application of zein-based biological carrier systems in functional foods, cosmetics, nutritional supplements, and pharmaceutical industries.

[0078] 2. Compared with the zein composite nanoparticles formed by protein modification alone, the zein composite nanoparticles modified with fructan have significantly improved physical and chemical stability, that is, they show excellent stability in temperature, pH and ionic strength at a temperature range of 40-90°C, a pH value of 2-8, and a NaCl concentration range of 40mM to 2M. In addition, the zein composite nanoparticles double-modified with fructan / protein show excellent redispersibility after freeze-drying. It can improve the encapsulation and drug loading efficiency of active ingredients, antioxidant activity, and absorption and distribution in the body, thereby improving the bioavailability of active ingredients.

[0079] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 The drug encapsulation efficiency and drug loading measurement results of the composite nanoparticles of Example 1 of the present invention;

[0081] Figure 2 The particle size distribution and zeta potential detection results of the composite nanoparticles of Example 1 of the present invention;

[0082] Figure 3 The FT-IR spectrum structure and XRD spectrum structure characterization results of the composite nanoparticles of Example 1 of the present invention;

[0083] Figure 4 The SEM and TEM contour structure characterization results of the composite nanoparticles of Example 1 of the present invention;

[0084] Figure 5 The in vitro release curves of different Ast nanoparticles were measured in a release medium composed of simulated gastrointestinal fluid using a dynamic dialysis method according to Example 1 of the present invention;

[0085] Figure 6 The redispersibility test results of Zein composite nanoparticles loaded with Ast in different modification modes according to Example 2 of the present invention;

[0086] Figure 7 The stability test results of Zein composite nanoparticles loaded with Ast in different modification modes according to Example 2 of the present invention;

[0087] Figure 8 The encapsulation efficiency of Zein / P-FOS / NaCas composite nanoparticles encapsulating Ast prepared with different P-FOS composition ratios in Example 3 of the present invention;

[0088] Fig. 9The particle size and zeta potential of the Zein / P-FOS / NaCas composite nanoparticles loaded with Ast prepared in different P-FOS composition ratios in Example 3 of the present invention before and after freeze-drying;

[0089] Fig.10 The test results of the effects of AZS and AZPS nanoparticles on the antioxidant activity of Ast in Example 4 of the present invention are as follows;

[0090] Fig.11 The cytotoxicity test results of Ast preparations of different concentrations in Example 4 of the present invention are shown;

[0091] Fig.12 The Ast serum drug concentration-time curves corresponding to the pharmacokinetic experimental results of different Ast preparations in Example 5 of the present invention. DETAILED DESCRIPTION

[0092] The present invention is further described in detail below with reference to examples so that those skilled in the art can implement the invention with reference to the description.

[0093] It should be understood that the terms "having", "comprising" and "including" used herein do not exclude the presence or addition of one or more other elements or their combinations. It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial sources unless otherwise specified.

[0094] Some of the reagents, materials, and experimental animals used in the experiments of the embodiments are as follows:

[0095] Astilbin (Ast, >98%) was purchased from Prefa Biotechnology Co., Ltd. (Chengdu, China). Food-grade zein, fructan, and sodium casein were purchased from MacLean Technology Co., Ltd. (Shanghai, China). Polysialic acid (PSA) was produced by Zhenjiang Changxing Pharmaceutical Co., Ltd. (Zhenjiang, China). CCK8 kit was provided by TargetMol (Shanghai, China). 1,1-Diphenyl-2-trinitrophenylhydrazine (DPPH) and reactive oxygen species (ROS) detection kits were purchased from Beyotime Biotechnology Co., Ltd. (Beijing, China). Unless otherwise specified, all other chemical reagents were used as received.

[0096] Mouse mononuclear macrophage RAW 264.7 cell line was obtained from Zhejiang Meisen Cell Technology Co., Ltd. (Zhejiang, China) and cultured in DMEM medium (Gibco, Thermofisher, USA) supplemented with 10% fetal bovine serum (Zhejiang Meisen Cell Technology Co., Ltd., Zhejiang, China), 100 U / mL penicillin and 100 μg / mL streptomycin at 37 °C in a humidified atmosphere containing 5% CO .

[0097] Statistical analysis:

[0098] All experimental results in the examples are expressed as mean ± standard deviation. Statistical differences were determined using Student's t test. p < 0.05 was considered to be significantly different, and p < 0.01 was considered to be extremely significantly different.

[0099] Example 1: Preparation and characterization of Zein composite nanoparticles loaded with Ast in different modification methods

[0100] 1. Preparation of Nanoparticles

[0101] The zein composite nanoparticles loaded with Ast were prepared by using P-FOS / NaCas dual modification and NaCas single modification, respectively. The specific steps are as follows:

[0102] Preparation of Ast / Zein mixed solution: Zein (100 mg) was dissolved in 5.0 mL of ethanol / water (75:25, v / v) and stirred magnetically (1000 rpm) for 30 min. Ast (50 mg) was dissolved in 5.0 mL of ethanol / water (75:25, v / v) and stirred magnetically (1000 rpm) for 30 min. 5 mL of AST solution was added dropwise to 5 mL of Zein solution and stirred for 0.5 h to obtain 10 mL of AST / Zein mixture.

[0103] Preparation of P-FOS / NaCas mixed solution: P-FOS (100 mg) was dissolved in 5.0 mL ultrapure water and stirred magnetically (1000 rpm) for 30 min. NaCas (200 mg) was dissolved in 30.0 mL ultrapure water and stirred magnetically (1000 rpm) for 1 h. 5 mL of P-FOS aqueous solution was added dropwise to 30 mL of NaCas solution and stirred for 1 h to obtain 35 mL of P-FOS / NaCas mixed solution.

[0104] For the method of double modification and coating Zein nanoparticles with P-FOS and NaCas, the obtained Ast / Zein mixed solution (10.0 mL) was injected into 35.0 mL P-FOS / NaCas mixed solution, and stirred (1000 rpm) for 1 hour. The suspension was evaporated and concentrated on a rotary evaporator (45°C) to remove ethanol to obtain an Ast / Zein / P-FOS / NaCas nanosuspension. The prepared sample suspension was centrifuged at a speed of 5000 r / min for 10 min to remove large particles and free Ast. The prepared sample was freeze-dried to obtain a nanoparticle powder, which is referred to as Ast / Zein / P-FOS / NaCas nanoparticles (AZPS) in the accompanying drawings.

[0105] For the method of NaCas modified Zein nanoparticles, the obtained Ast / Zein mixed solution (10.0 mL) was injected into 30.0 mL NaCas solution, and the mixture was continuously stirred (1000 rpm) for 1 hour. The suspension was evaporated and concentrated on a rotary evaporator (45°C) to remove ethanol to obtain an Ast / Zein / NaCas nanosuspension. The prepared sample suspension was centrifuged at a speed of 5000 r / min for 10 min to remove large particles and free Ast. The prepared sample was freeze-dried to obtain a nanoparticle powder, which is referred to as Ast / Zein / NaCas nanoparticles (AZS) in the accompanying drawings.

[0106] The molecular weight of the P-FOS used above is 1600-2000Da.

[0107] The mass composition ratio of Ast / Zein / P-FOS / NaCas used above is 1:2:3:4.

[0108] 2. Experimental results

[0109] 2.1. Encapsulation efficiency, drug loading and particle size

[0110] The drug encapsulation efficiency (EE) and loading capacity (LC) of Zein composite nanoparticles were determined by HPLC-MS / MS system. The calculation formula of EE is as follows: EE = (weight of Ast loaded / weight of total Ast fed) × 100%. The calculation formula of LC is as follows: LC = (weight of Ast loaded / weight of nanoparticles) × 100%. The average particle size (Particle Diameter), polydispersity index (PDI) and zeta potential value (Zeta) of different nanoparticles were analyzed by dynamic laser particle size analyzer (DLS, Zetasizer NANO ZSP, Malvern).

[0111] The experimental results are as follows Figure 1 As shown in the figure, the encapsulation efficiency and drug loading of Zein nanoparticles (AZS) modified with NaCas for Ast were 73.56±1.62% and 13.3±1.13%, respectively. When double modified with fructan P-FOS and NaCas, the encapsulation efficiency of Zein nanoparticles (AZPS) for Ast was significantly improved, with an encapsulation efficiency of 92.34±1.28% and a drug loading of 12.4±0.93%, indicating that the cross-linking of fructan P-FOS can promote the encapsulation efficiency of Zein / NaCas composite nanoparticles for hydrophobic active ingredients.

[0112] like Figure 2As shown, the particle size distribution obtained by dynamic light scattering detection shows that both AZPS and AZS have narrow particle size distribution, and there is no significant difference in the particle size (Particle Diameter) of AZS and AZPS, with an average size of 160nm, and a particle size distribution index (PDI) of less than 0.2, indicating that the obtained Zein nanoparticles have good dispersibility. At the same time, the cross-linking of fructan P-FOS has little effect on the particle size of Zein / NaCas composite nanoparticles, indicating that P-FOS has been successfully introduced into the interior of zein / NaCas composite nanoparticles.

[0113] The zeta potential of AZS was measured to be -25.2±2.2mV. After modification with P-FOS, the zeta potential of AZPS was -27.8±2.8mV. Since P-FOS is a neutral polysaccharide and there is no carboxyl or amino group in the chemical structure, the addition of P-FOS did not significantly change the charge of the nanoparticles, but the absolute value increased slightly, indicating that P-FOS was successfully introduced into the interior of the zein / NaCas composite nanoparticles, increasing the steric repulsion through hydrogen bonds and hydrophobic interactions between zein and NaCas, weakening the electrostatic adsorption force between zein and NaCas, thereby increasing the absolute value of the zeta potential. The relatively high zeta potential is a key factor in improving the stability of nanoparticles in aqueous media through electrostatic repulsion. In general, negatively charged nanoparticles may exhibit improved nanocolloid stability, increased blood circulation time, and reduced toxicity to normal cells compared to positively charged nanoparticles.

[0114] 2.2 Characterization of Nanoparticles

[0115] FT-IR spectroscopy structural characterization of Zein composite nanoparticles Figure 3 -A shows that for Zein, the main characteristic peak in the FT-IR spectrum is at 3292 cm -1 A broad band is shown at 1640.7 cm, which is attributed to the overlapping stretching vibrations of -NH and -OH. -1 、1515.1cm -1 and 1446.1cm -1 The peaks at 3292 cm-1 are related to the CO stretching vibration of amide I, the NH bending vibration of amide II, and the -CH2 stretching vibration. -1 The Zein peaks at 3273.80 cm -1 and 3280.23cm -1 , while the peaks associated with amide I shifted to 1637.8 and 1638.9 cm -1 , the peaks associated with amide II shifted to 1514.7 and 1525.5 cm -1 . Zein at 3292cm-1 The shift at 1640 cm-1 is related to the formation of intermolecular hydrogen bonds, while the -1 and 1515cm -1 The peak moving at 1631.8cm corresponds to the electrostatic interaction between molecules. The results show that electrostatic interaction and intermolecular hydrogen bonding are involved in the co-assembly process of Zein / P-FOS / NaCas composite nanoparticles. In the FT-IR spectrum of free Ast, 1631.8cm -1 、1601.3cm -1 、1524.5cm -1 、1503.8cm -1 and 1473.2cm -1 The peaks at 1350, 1290.75, and 1173.74 cm cm are consistent with the presence of the aromatic ring and -C=O group extension. The inter-ring chain portion of Ast and the CCC, CCH, and COC vibrations of the aromatic ring are reflected at 1350, 1290.75, and 1173.74 cm cm -1 , while these peaks disappeared in the FT-IR spectra of AZS and AZPS, indicating that Ast was encapsulated in the Zein composite nanoparticles.

[0116] The XRD spectrum structure characterization of Zein composite nanoparticles is as follows Figure 3 -B, the XRD spectrum of Ast monomer shows characteristic peaks at diffraction angles (2θ) of 5-50°, which is related to its crystalline state. However, these characteristic peaks disappeared in the XRD spectra of AZS and AZPS. This shows that Ast is encapsulated in Zein composite nanoparticles in an amorphous state. P-FOS shows a broad peak at around 19.5, while Zein and NaCas show two broad peaks at 10.5 and 22.9, indicating that Zein, NaCas, and P-FOS are all amorphous. After the formation of composite nanoparticles, the intensity of the Zein diffraction peak decreases, indicating that there is an interaction between Zein, NaCas, and P-FOS. It is worth noting that AZS and AZPS NPs have similar XRD behaviors, which indicates that the cross-linking of P-FOS in AZPS nanoparticles has no significant effect on the amorphous structure of Zein / NaCas composite nanoparticles, which is consistent with the experimental results observed by DLS.

[0117] The size, structure and morphology of the nanoparticles were confirmed by field emission scanning electron microscopy (SEM, Zeiss Gemini 300, Japan) and transmission electron microscopy (TEM, FEI Tecnai G2 F30, Japan).

[0118] SEM and TEM structural characterization of Zein composite nanoparticles Figure 4As shown, the TEM images of AZPS and AZS show a clear core-shell spherical structure with an average size of 140 nm (there is a deviation between the particle size measured by TEM and the particle size measured by the nanoparticle size analyzer, which is within a reasonable error range), which is consistent with the experimental results observed by DLS.

[0119] 2.3. Simulated gastrointestinal fluid release

[0120] The in vitro release profiles of different Ast nanoparticles were determined in a release medium consisting of simulated gastrointestinal fluid using a dynamic dialysis method.

[0121] Simulated gastric fluid: The sample was dispersed in 2 mL of simulated gastric fluid (SGF, pH 2.0, containing pepsin) to a concentration of 0.8 mg / mL of Ast. The sample was then transferred to a dialysis bag with SGF as the dialysis medium (molecular weight cutoff: 3500 Da), dialyzed in 30 mL of release medium, placed in a water bath, and then stirred at 110 rpm at 37 ° C. During the digestion process, 100 μL of external medium was collected at regular intervals and supplemented with the same volume of fresh medium to maintain a constant volume. The gastric digestion phase lasted 120 minutes.

[0122] Simulated intestinal fluid: After the gastric fluid phase, the remaining fluid was mixed with an equal volume of small intestinal fluid (SIF, pH 7.0, containing 8.5 mg / mL pancreatin), and then the pH was adjusted to 7.0 with NaOH solution (2M). The resulting fluid was dialyzed against 30 mL of release medium, and then stirred at 110 rpm in a 37°C water bath. During the digestion process, 100 μL of external medium was collected at regular intervals and supplemented with the same volume of fresh medium to maintain a constant volume. The simulated intestinal fluid digestion phase lasted for 120 minutes.

[0123] The samples collected at different digestion stages were heated to 90°C for 5 min to inactivate the digestive enzymes, then diluted with 1 mL of methanol and centrifuged at 13,000 rpm / min for 10 min. The Ast content in the external medium was determined within 2 h using an HPLC-MS / MS system.

[0124] like Figure 5As shown in the figure, the release efficiency of different Ast preparations gradually and steadily increased in the simulated gastric fluid stage, among which AZS and AZPS were significantly higher than free Ast. After 60 minutes, free Ast, AZS, and AZPS released about 32.5%, 55.6%, and 76.3% of Ast, respectively, of which AZPS was close to 100% released at 2h. The release rate of free Ast is relatively low because its crystal structure hinders its dispersibility in gastrointestinal fluid. In contrast, in AZS and AZPS nanoparticles, Ast exists in an amorphous form, which contributes to its release behavior. It is worth noting that the release rate of Ast in AZS is delayed compared with AZPS. This may be due to the stronger electrostatic interaction between Zein and NaCas in AZS, and Ast is embedded in the hydrophobic region of Zein, resulting in a more compact microstructure of the particles and lower hydration efficiency. In contrast, the introduction of hydrophilic P-FOS into the Zein matrix in AZPS can generate multiple intermolecular hydrogen bonds between Zein and NaCas, reduce the hydrophobicity of the particle matrix, and improve its hydration efficiency, which ultimately enables Ast to have the greatest stability and the most efficient release behavior in gastrointestinal fluid, indicating that AZPS has better bioavailability in gastrointestinal fluid.

[0125] Example 2: Investigation of the stability and redispersibility of Zein composite nanoparticles loaded with Ast in different modification methods

[0126] 1. Stability and redispersibility

[0127] The challenges faced by Zein-based nanocarriers are redispersibility and stability under different environmental conditions, such as high temperature, ionic strength and pH challenges in the manufacturing process of food, cosmetics, health food and pharmaceutical products. Therefore, the present invention compares and tests the redispersibility of Zein composite nanoparticles loaded with Ast in different modification modes and the influence of various environmental pressures on the stability of the composite particles.

[0128] 1.1. Redispersibility

[0129] The Zein composite nanoparticle samples with different modifications before and after freeze-drying were redispersed in ultrapure water, and the average particle size and PDI value were measured. Figure 6 As shown in the figure, AZPS generally maintains the same particle size after freeze-drying, while the ζ potential remains at about -25mV and the PDI value is less than 0.2. In contrast, the particle size of AZS increases from 179nm to 250nm after freeze-drying. This shows that AZPS nanoparticles have good redispersibility before and after freeze-drying, and have a narrow particle size distribution. It shows that P-FOS cross-linking can significantly improve the redispersibility of Zein / NaCasNPs. In the figure, freeze-drying before is before freeze-drying, and freeze-drying later is after freeze-drying.

[0130] 1.2 Stability investigation

[0131] Ionic strength stability

[0132] Sodium ions are usually added during the manufacturing process. Sodium ions can shield the net surface charge of protein particles, thereby reducing the electrostatic repulsion between particles, causing Zein nanoparticles to be unstable and prone to aggregation. Figure 7 As shown, AZS nanoparticles are highly sensitive to NaCl solutions. After adding NaCl solutions of different concentrations, AZS nanoparticles aggregated and precipitated in large quantities. This indicates that the electrostatic repulsion between Zein and NaCas in AZS is weakened due to the shielding effect of sodium ions. In contrast, the particle size of AZPS nanoparticles was not significantly affected in a wide range of NaCl ion strength (40mM to 2M), the particle size change was not obvious, and the distribution was uniform (PDI<0.25), although the zeta potential dropped to near net zero electric repulsion ( Figure 7 ). Sodium ions will shield the surface charge of protein particles, resulting in a decrease in zeta potential. In this study, AZPS showed good resistance to ionic strength, indicating that the cross-linking of P-FOS can significantly enhance the spatial repulsion effect of zein composite nanoparticles, thereby obtaining more stable and uniform zein composite nanoparticles.

[0133] pH stability

[0134] Zein nanoparticles may experience different pH environments during manufacturing, storage, and administration. However, protein particles are generally sensitive to pH changes. In general, the surface charge of the particles decreases near the isoelectric point of the protein, which minimizes the electrostatic repulsion between protein particles and promotes aggregation. Figure 7It was shown that since zein and NaCas are sensitive to pH changes and their isoelectric points are pH 6.2 and 4.2, respectively, AZS nanoparticles show obvious aggregation in the pH range of 3 to 8. The zeta potential of particles close to the isoelectric point is relatively low, and the electrostatic repulsion is very weak, resulting in obvious particle aggregation; while AZPS nanoparticles can still maintain a relatively stable state even near the isoelectric points of zein and NaCas (pH 6.2 and 4.2). When the nanoparticles were incubated at pH 3, a slight increase in particle size was observed. This may be due to the weakening of electrostatic interactions between proteins and the protonation of P-FOS, in which the three polymers repel each other, resulting in the expansion of the polymer network, which significantly increases its hydrodynamic diameter. However, at pH 3, the PDI value of AZPS nanoparticles is still small (<0.2), indicating that the particles have a stable and narrow particle size distribution. Since the electrostatic repulsion is weakened near the isoelectric point of Zein nanoparticles, the steric repulsion can be not significantly affected by changes in environmental conditions. Therefore, it is further demonstrated that P-FOS stabilizes the Zein / NaCas composite nanoparticles by increasing the steric repulsion, thus exhibiting a more stable and uniform colloidal solution in the pH range of 2–8.

[0135] Thermal stability

[0136] In order to verify the stability of the composite particles under heating conditions, AZS and AZPS composite nanoparticles were suspended in ultrapure water at a concentration of 1.0 mg / mL and incubated at temperatures of 40, 50, 60, 70, 80, and 90°C for 30 min. Figure 7 As shown, when the temperature exceeds 50°C, the AZS group shows obvious agglomeration. On the contrary, the AZPS group shows good colloidal stability and a narrow particle size distribution (PDI < 0.3). Even when the temperature rises to 90°C, no obvious agglomeration phenomenon is observed. This shows that AZPS has significantly improved thermal stability relative to AZS. At 90°C, the particle size of AZPS increases from the original 205nm to about 320nm, which may be due to the partial unfolding of the zein molecules at high temperatures. In the present invention, heating the AZPS nanoparticles at 90°C for 30 minutes only causes the nanoparticle size to increase to a certain extent, but still maintains a stable colloidal solution with good uniformity, which further verifies the stabilizing effect of P-FOS on Zein composite nanoparticles.

[0137] Overall, the above stability study results show that P-FOS can significantly improve the stability of Zein / NaCas nanoparticles against various environmental stresses (i.e., pH changes, high temperatures, and ionic strength). P-FOS increases the steric repulsion between Zein and NaCas through a cross-network of hydrophilic carbohydrate layers and improves the hydration of hydrophobic Zein nanoparticles, thereby improving stability and dispersibility in aqueous environments.

[0138] Example 3: Investigation of P-FOS composition ratio

[0139] 1. Preparation of Nanoparticles

[0140] Zein / P-FOS / NaCas composite nanoparticles loaded with Ast were prepared using different P-FOS composition ratios. The specific steps are as follows:

[0141] Preparation of Ast / Zein mixed solution: Zein (100 mg) was dissolved in 5.0 mL of ethanol / water (75:25, v / v) and stirred magnetically (1000 rpm) for 30 min. Ast (50 mg) was dissolved in 5.0 mL of ethanol / water (75:25, v / v) and stirred magnetically (1000 rpm) for 30 min. 5 mL of AST solution was added dropwise to 5 mL of Zein solution and stirred for 0.5 h to obtain 10 mL of AST / Zein mixture.

[0142] Preparation of P-FOS / NaCas mixed solution: P-FOS (100 mg) was dissolved in 5.0 mL ultrapure water and stirred magnetically (1000 rpm) for 30 min. NaCas (200 mg) was dissolved in 30.0 mL ultrapure water and stirred magnetically (1000 rpm) for 1 h. 5 mL of P-FOS aqueous solution was added dropwise to 30 mL of NaCas solution and stirred for 1 h to obtain 35 mL of P-FOS / NaCas mixed solution.

[0143] For the method of modifying Zein composite nanoparticles with P-FOS, the obtained Ast / Zein mixed solution (10.0 mL) was injected into 35.0 mL P-FOS / NaCas mixed solution, and the mixture was stirred (1000 rpm) for 1 hour. The suspension was evaporated and concentrated on a rotary evaporator (45°C) to remove ethanol to obtain an Ast / Zein / P-FOS / NaCas nanosuspension. The prepared sample suspension was centrifuged at a speed of 5000 r / min for 10 minutes to remove large particles and free Ast. The prepared sample was freeze-dried to obtain a nanoparticle powder, which was called Ast / Zein / P-FOS / NaCas nanoparticles.

[0144] The composition ratios of the above-mentioned Ast / Zein / P-FOS / NaCas are 1:2:1:4, 1:2:2:4, 1:2:3:4, 1:2:4:4, and 1:2:5:4, respectively.

[0145] The size, potential and distribution of the nanoparticles were confirmed by a dynamic laser sizing analyzer (DLS, Zetasizer NANO ZSP, Malvern).

[0146] 2. Experimental results

[0147] The experimental results are as follows Figure 8 As shown, when the relative mass proportion of P-FOS is increased, the particle size increases slightly with the increase of P-FOS proportion (170-200 nm), but the increasing trend of the encapsulation rate of nanoparticles is not obvious.

[0148] At the same time, by comparing the particle size of nanoparticles before and after freeze-drying ( Fig. 9 A), Zein / NaCas composite nanoparticles composed of different proportions of P-FOS have good redispersibility, and the absolute value of the zeta potential of the nanoparticles is between 20 and 25 mV ( Fig. 9 B), indicating that the nanoparticles have good stability. In addition, P-FOS is a neutral polysaccharide with self-assembly characteristics. The multi-hydroxy and β (1-2) flexible fructose glycosidic bond structure determines that the cross-linking process between P-FOS and cationic Zein and anionic NaCas belongs to non-covalent bond (mainly through hydrogen bonds and hydrophobic interactions) co-assembly physical cross-linking. For Zein / NaCas composite nanoparticles cross-linked with P-FOS at different mass ratios, the negative ζ potential of the nanoparticles was not reversed, and the absolute value was 20-25mV, with no obvious change, indicating that the P-FOS cross-linking is mainly located inside zein and NaCas. In the figure, freeze-drying before is before freeze-drying, and freeze-drying later is after freeze-drying.

[0149] Example 4: Investigation of the antioxidant activity of different Ast preparations

[0150] Ast has good antioxidant activity, however, its in vivo activity and bioavailability are limited due to its poor water solubility. In order to study the enhancing effect of P-FOS cross-linked Zein / NaCas composite nanoparticles on the bioactivity of encapsulated active substances, the effects of AZS and AZPS nanoparticles on the antioxidant activity of Ast were evaluated in this paper.

[0151] DPPH free radical scavenging assay

[0152] 1. Experimental methods

[0153] Briefly, DPPH (2 mg) was dissolved in ethanol (5 mL) to obtain a DPPH stock solution. The stock solution was then diluted with ethanol to obtain a DPPH working solution with a concentration between 0.1 and 2.0 mM. Then, 100 μL of the diluted working solution was added to the designated wells in a 96-well microplate, followed by 100 μL of sample or control solution. The microplate was placed in the dark for 30 minutes, and then the absorbance was read at 517 nm using a Thermo Scientific Varioskan Flash microplate reader (Thermo, USA).

[0154] 2. Experimental results

[0155] like Fig.10 As shown in Figure A, when the Ast concentration was 50, 100, 150 and 200 μg / ml, AZPS nanoparticles were able to inhibit 28.7%, 62.7%, 80.5% and about 90% of superoxide radicals. At the same time, AZPS showed a more significant free radical scavenging effect than free Ast monomer and AZS. This can be explained by the good dispersibility and bioaccessibility of AZPS. The free radical scavenging efficiency is related to the dissolution and release rate of Ast. The cross-linking of hydrophilic P-FOS promotes the hydration and dispersibility of the hydrophobic Zein matrix in the aqueous environment, thereby enhancing the dissolution of Ast and achieving a higher Ast equilibrium concentration, allowing better contact between superoxide radicals and Ast. On the other hand, due to the electrostatic interaction between Zein and NaCas, AZS particles have a more compact core-shell structure, which hinders the release of Ast in aqueous solution, so AZPS has a more significant free radical scavenging efficiency than AZS nanoparticles.

[0156] Intracellular reactive oxygen species (ROS) test

[0157] A cell model was further used to evaluate the ability of AZPS to regulate intracellular ROS levels. Human macrophages are key coordinators of the onset and resolution phases of inflammation, and are also sentinel cells that maintain homeostasis and prevent infection. The stimulation of macrophages induces inflammatory responses that prompt them to undergo various cellular changes, among which the production of reactive oxygen species ROS plays a key role in the differentiation and activation of macrophages. The present invention applies Gram-negative bacterial lipopolysaccharide (LPS) to mouse mononuclear macrophages (RAW 264.7) to promote oxidative stress and produce ROS, and detects the ability of different Ast preparations (Ast monomer, AZS and AZPS nanoparticles) to regulate intracellular ROS levels.

[0158] 1. Experimental methods

[0159] Cytotoxicity assay

[0160] CCK8 assay was used to evaluate the viability of RAW 264.7 cells after 24 h of treatment with different concentrations of Ast preparations (free Ast, AZS and AZPS). Briefly, RAW 264.7 cells were cultured in DMEM medium containing 10% FBS, 1% penicillin-streptomycin solution and placed in an incubator at 37°C and 5% CO2.

[0161] RAW 264.7 cells were plated at approximately 1 × 10 4 The cells were seeded in a 96-well plate at a density of 1.50 μg / mL and incubated for 24 h. A series of Ast preparation solutions with different Ast concentrations (1-20 μg / mL) were prepared in serum-free medium.

[0162] The cells were treated with different concentrations of Ast preparations. After incubation for 24 h, the culture medium was discarded and the cells were washed twice with phosphate buffered saline (PBS).

[0163] According to the instructions provided by the manufacturer, the cytotoxicity of the three Ast preparations was determined using the CCK-8 method. The cells in each well were treated with 10% CCK8 and incubated for another 2 hours at 37°C, and the absorbance of the final solution representing cell viability was measured using a Thermo Scientific Varioskan Flash microplate reader (Thermo, USA). Vitality was expressed as a percentage of the control group.

[0164] Determination of intracellular ROS

[0165] The fluorescent probe DCFH-DA was used to detect the intracellular ROS level. Briefly, RAW 264.7 cells were cultured at 1×10 5 The cells were seeded at a density of 100 cells / well in a 6-well cell culture plate and incubated for 24 h.

[0166] The cells were treated with three Ast preparations (5, 10, 20 μg / mL) at increasing concentrations for 2 h and then stimulated with LPS (5 μg / mL). The positive group was cells stimulated with LPS (5 μg / mL) without drug pretreatment, and the control group was treated with normal culture medium.

[0167] After 24 h of incubation, all the medium was carefully removed, and then the cells were incubated with 10 μM DCFH-DA for 30 min at 37° C. The cells were then rinsed twice with PBS to completely remove the DCFH-DA that had not entered the cells.

[0168] The cells were collected and analyzed by flow cytometry (Guava Fluorescence intensity was analyzed by a microplate reader (Infinite M200 Pro, Tecan, Austria) with an excitation wavelength of 488 nm and an emission wavelength of 525 nm. Relative fluorescence intensity was calculated compared with the control (cells not treated with LPS).

[0169] 2. Experimental results

[0170] like Fig.11 As shown in the results, no obvious cytotoxicity was observed in all groups when the Ast concentration ranged from 1 to 20 μg / mL. Therefore, this dose range is suitable for further study.

[0171] DCFH-DA was used as a fluorescent probe to monitor the intracellular ROS level.

[0172] like Fig.10 B and Fig.10 As shown in C, compared with the untreated group, LPS stimulation led to an increase in the fluorescence intensity of DCF in RAW 264.7 cells, indicating that the level of ROS was enhanced. Compared with the Ast monomer and AZS treatment groups, the AZPS treatment group significantly reduced the fluorescence intensity of DCF, indicating that AZPS pretreatment more effectively reduced the upregulation of ROS generation in RAW 264.7 cells caused by LPS stimulation. This result is consistent with the results of the in vitro DPPH free radical scavenging assay. Therefore, the ability of AZPS to inhibit ROS levels in LPS-stimulated RAW 264.7 macrophages may be related to its free radical scavenging ability. These results indicate that P-FOS-crosslinked zein / NaCas composite nanoparticles can effectively enhance the antioxidant activity of hydrophobic bioactive substances.

[0173] Example 5: Pharmacokinetic experiments on different Ast preparations to promote oral absorption

[0174] 1. Experimental methods

[0175] Male SD rats weighing 250-300 g were randomly divided into an Ast monomer group, an AZS group, and an AZPS nanoparticle group, with 6 rats in each group. The two groups of rats were intragastrically administered as follows:

[0176] Adaptive feeding was performed before the experiment, and the mice were fasted but not watered for 12 hours before administration and fasted but not watered for 2 hours after administration. Each group was gavaged with Ast20mg / kg.

[0177] After oral administration, 0.5 mL of blood was collected from the orbit at 0.167 h, 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, and 24 h, respectively, and placed in EP centrifuge tubes. After stratification at room temperature (about 2 h), the tubes were centrifuged (2000 r / min) and the samples were centrifuged. -1, 15min), repeat twice, take the upper layer of serum, seal it and store it in a -80℃ refrigerator for later use.

[0178] The blood concentration of Ast was detected by HPLC-MS / MS, and the area under the drug concentration-time curve and relative bioavailability were calculated.

[0179] 2. Experimental results:

[0180] like Fig.12 Shown is the Ast serum drug concentration-time curve corresponding to the pharmacokinetic experimental results.

[0181] The corresponding pharmacokinetic parameters of the three groups of experiments, Ast monomer group, AZS group and AZPS nanoparticles, are shown in Table 1.

[0182] Table 1 Pharmacokinetic parameters of AST group, AZS group and AZPS group at an oral dose of 20 mg / kg (results are expressed as mean ± SD)

[0183] Group <![CDATA[T 1 / 2 (h)]]> <![CDATA[C max (ng / mL)]]> <![CDATA[T max (h)]]> <![CDATA[AUC (0-24) (ng / ml*h)]]> AST group 8.455±7.265 31.982±19.645 1.564±2.673 101.137±63.269 AZS group 4.276±2.794 39.769±17.081 1.918±1.818 149.777±40.991 AZPS Group 4.272±2.317 <![CDATA[94.214±58.177 △△ ]]> 1.105±1.311 <![CDATA[299.150±109.662 △△ ]]>

[0184] Note: AST vs AZS P<0.05:*; P<0.01:**

[0185] AST vs AZPS P<0.05: △ ; P<0.01: △△

[0186] As can be seen from Table 1, compared with Ast monomer and AZS, the oral AZPS nanoparticles provided by the present invention can significantly improve the oral absorption of Ast, and the oral relative bioavailability of Ast is about 3 times higher than that of Ast monomer, and about 2 times higher than that of AZS without the addition of fructan P-FOS cross-linking.

[0187] In summary, the inventors have successfully used the anti-solvent co-assembly precipitation technology for the first time to prepare a fructan (P-FOS) and protein co-modified zein core / shell nanoparticles, which can be used to efficiently encapsulate hydrophobic active ingredients (such as astilbin (Ast)), which can significantly enhance the stability of zein under different environmental pressures (pH, temperature, ionic strength), improve the encapsulation and drug loading efficiency of active ingredients, and the absorption and distribution in the body, thereby improving the bioavailability of active ingredients. Taking Ast as an example, experiments have shown that Ast / Zein / P-FOS / NaCas (AZPS) nanoparticles have excellent stability and redispersibility under different environmental pressures (pH, temperature, ionic strength). In addition, AZPS nanoparticles significantly improve the dissolution and release of Ast in simulated gastrointestinal fluid, thereby producing stronger antioxidant activity. AZPS is a biosafe and biocompatible nanodrug delivery system that is non-toxic to mouse mononuclear macrophages and can regulate the level of reactive oxygen species stimulated by inflammation. Therefore, the fructan (P-FOS) and protein co-modified zein core / shell nanoparticles prepared by the present invention are expected to become an effective hydrophobic active ingredient carrier for food, health products, cosmetics and drug development.

[0188] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

[0189] The aforementioned embodiments and methods described in the present invention may be varied based on the ability, experience and preference of those skilled in the art.

[0190] In the present invention, merely listing the steps of the method in a certain order does not constitute any limitation on the order of the method steps.

Claims

1. A composite nanoparticle, It is characterized in that include: core particles, formed by zein; The coating layer is formed by fructan and ionic polymer.

2. The composite nanoparticles according to claim 1, It is characterized in that The average molecular weight of the fructan is 800-150000Da; the particle size of the composite nanoparticle is 100-300nm; the thickness of the coating layer is 1-100nm; the particle size of the core particle is 50-120nm; and the composite nanoparticle is negatively charged.

3. A method for preparing the composite nanoparticles according to claim 1, It is characterized in that The process includes forming core particles and forming a coating layer, specifically including: Dissolving zein in an ethanol aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a zein ethanol mixed solution; Dissolving fructan and sodium caseinate in an aqueous solution, stirring, adjusting the pH to acidic, and stirring to obtain a fructan and sodium caseinate mixed solution; The obtained zein ethanol mixed solution is mixed with the obtained fructan and sodium caseinate mixed solution, the pH is adjusted to acidic, stirred to obtain a solution system, ethanol and impurities are removed, and dried to obtain composite nanoparticles.

4. Use of the composite nanoparticles according to claim 1 or the composite nanoparticles prepared by the preparation method according to claim 4 as drug carriers or in the preparation of drugs, cosmetics or nutritional health products.

5. A vector delivery system, It is characterized in that The composite nanoparticles according to claim 1 or containing the composite nanoparticles, wherein the core particles of the composite nanoparticles are loaded with one or more active ingredients.

6. The carrier delivery system according to claim 6, It is characterized in that The active ingredient is astilbin; in the core particles, the weight ratio of zein to astilbin is 2:

1.

7. A method for preparing the carrier delivery system according to claim 6, It is characterized in that include: 1) forming core particles with zein and active ingredients; 2) Forming a coating layer.

8. A pharmaceutical composition for improving the stability, redispersibility, encapsulation rate, release efficiency or pharmacological activity of drug-encapsulated components, It is characterized in that The invention comprises the carrier delivery system according to claim 6, and one or more pharmaceutically acceptable excipients.

9. A nutritional health product, It is characterized in that The invention comprises the carrier delivery system according to claim 6, and one or more excipients acceptable for nutritional health products.

10. A cosmetic product, It is characterized in that The invention comprises the carrier delivery system according to claim 6, and one or more cosmetically acceptable excipients.

Citation Information

Patent Citations

  • Novel food-based nano-particle with core-shell structure and construction method thereof

    CN113875969A

  • Natural active substance-corn protein nanoparticle and preparation method and application thereof

    CN114796155A